2016
DOI: 10.4103/0028-3886.177611
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Magnetic Resonance Parkinsonism Index in differentiating progressive supranuclear palsy from Parkinson's disease and controls in Indian patients

Abstract: Magnetic Resonance Parkinsonism Index is more sensitive, specific, and accurate in differentiating PSP from PD in the early stages on an individual basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
3
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(57 citation statements)
references
References 0 publications
4
47
3
3
Order By: Relevance
“…In the past few years, MRPI has been widely proposed to support clinicians in the difficult task of differentiating clinically patients with PSP from those with PD or those with other parkinsonisms . A recent study from the MDS‐endorsed group for PSP stated that the P/M and MRPI were the most reliable biomarkers for diagnosing PSP‐RS both in the early and late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past few years, MRPI has been widely proposed to support clinicians in the difficult task of differentiating clinically patients with PSP from those with PD or those with other parkinsonisms . A recent study from the MDS‐endorsed group for PSP stated that the P/M and MRPI were the most reliable biomarkers for diagnosing PSP‐RS both in the early and late stages of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance (MR) imaging measurements have been shown to be useful for diagnosing PSP . The MR Parkinsonism Index (MRPI) has proven to be an accurate biomarker for diagnosing patients with PSP and for predicting the clinical evolution toward PSP phenotypes of patients affected by undetermined parkinsonism or the appearance of vertical supranuclear gaze palsy (VSGP) in patients with PSP‐P . Overall, this biomarker is highly accurate in diagnosing PSP‐RS but shows a low sensitivity in distinguishing between patients with PSP‐P and those with PD .…”
mentioning
confidence: 99%
“…In this study an MRPI cutoff score of ≥13.625 was used . Other studies that identified a similar sensitivity and specificity have used MRPI cutoffs ranging from ≥12.4 to ≥13.58 …”
Section: Resultsmentioning
confidence: 97%
“…Other measures were used to distinguish PSP in seven studies . There were 13 studies which reported MRI findings with ≥95% sensitivity and specificity for PSP (see Table ) . Of the 70 studies identified, only four studies determined the specificity/sensitivity of a MRI feature for predicting a pathological diagnosis of PSP (see Table ) …”
Section: Resultsmentioning
confidence: 99%
“…These findings are at variance with several previous studies reporting better performances of some measurements, such as midbrain/pons ratio and MRPI, in distinguishing patients with PSP from those with MSA and PD. In the last few years, many studies evaluated the midbrain/pons ratio and MRPI for differentiating patients with PSP from those with PD showing a high sensitivity and specificity (>85 and up to 100%) …”
mentioning
confidence: 99%